AgriTech4Egypt: Demo day | Session recording | A4IP - Zaccari, Claudia; Menza, Gianpiero (2024)
Demo Day celebrated the journey of 15 Agri-Tech innovation teams selected from a pool of over 900 global applicants, who have successfully completed an intensive 5-month acceleration program, combining business training and technical assistance, to transform Egyptian food systems.